2016
DOI: 10.1002/pd.4797
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of prenatal ultrasound findings in newborns with a Noonan spectrum disorder

Abstract: Objectives Noonan spectrum disorders (NSDs) occur in 1:1000-2500 live births. Currently, there are no guidelines for prenatal molecular genetic testing for NSDs. Recent studies recommend prenatal testing for NSDs when ultrasonography detects two or more associated abnormalities. A stronger association between ultrasound findings and NSDs would enable more informed prenatal genetic testing.Methods A total of 212 newborns (0-12 weeks) with prenatal ultrasound findings and a clinical suspicion of a NSD were refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
5
33
2
1
Order By: Relevance
“…Therefore, they are easily overlooked in pregnancy and might not be confined to only fetuses with a RIT1 mutation. SOS1 has to our knowledge only been described a handful of times before in the prenatal setting, 15 and in our study only one fetus showed a pathogenic variant. This…”
Section: Genesmentioning
confidence: 37%
“…Therefore, they are easily overlooked in pregnancy and might not be confined to only fetuses with a RIT1 mutation. SOS1 has to our knowledge only been described a handful of times before in the prenatal setting, 15 and in our study only one fetus showed a pathogenic variant. This…”
Section: Genesmentioning
confidence: 37%
“…This highlights the importance of RD testing when NT is clearly abnormal, as clinicians can provide a definitive diagnosis and inform parents regarding recurrence risk, especially when there are additional ultrasound findings. The inclusion in previous studies of pregnancies already suspected to have RD may be a reason for the lower detection rate in our study. A recent study with a clinical algorithm similar to ours showed a 10.3% (4/39) detection rate.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies testing for RD in cases with increased NT showed an incidence of 10%-26% 14,15,29 . In this study cohort, there was a 2.9% detection rate of pathogenic variants on RD testing, all of which were de novo and were detected in cases with NT > 6.0 mm.…”
Section: Discussionmentioning
confidence: 94%
“…The most common single‐gene disorder contributing to cardiac anomalies is Noonan syndrome (NS). Prenatally, a congenital heart defect like pulmonary valve stenosis was the most common fetal finding detected in molecularly confirmed NS newborns, followed by cystic hygroma and then increased nuchal translucency (Croonen, Nillesen, Stuurman, & Yntema, ; Hakami, Dillon, Lebo, & Mason‐Suares, ). From the findings of our study and literature review, the most familiar and representative intrauterine phenotypes of WBS were IUGR combined with cardiovascular abnormalities (particularly with SVAS).…”
Section: Discussionmentioning
confidence: 99%